Correlation Between LTC4S -444 A>C Polymorphism and Susceptibility to Asthma: A Meta-analysis and Trial Sequential Analysis: LTC4S polymorphism and susceptibility to asthma - Wu, Delin; Liu, Yuna; Liu, Yan; Cui, Najuan; Zhu, Yan; Zheng, Sidao; Wang, Shaohua (Journal of Medical Biochemistry, 2023)
Background: This study aims to uncover the potential correlation between LTC4S -444 A>C polymorphism and susceptibility to asthma. Methods: Literatures reporting the correlation between LTC4S -444 A>C polymorphism and susceptibility to asthma published before 1st June, 2019 were searched in PubMed, Embase, Cochrane, Wanfang and CNKI. Eligible literatures were enrolled and their data were extracted. OR and its 95%CI were calculated for assessing the correlation between LTC4S -444 A>C polymorphism and susceptibility to asthma. The included data were weighted by an inverse variance and then analyzed by a fixed or random effects model. Heterogeneity test and sensitivity analysis were performed on the enrolled reports. STATA12.1 and TSA (trial sequential analysis) were utilized for analyses.   Results: Fifteen studies involving 3,791 asthma patients and 2,185 healthy controls were enrolled. No significant correlation was found between the LTC4S -444 A>C polymorphism and susceptibility to asthma according to the results of different models ((Dominant model (D): OR=1.10, 95%CI=0.98-1.23; Recessive model (R): 1.07, 0.84-1.36; Homozygous model (Homo): 1.11, 0.87-1.41; Heterozygous model (Hetero): 1.10, 0.98-1.24; Allele model (A): 1.07, 0.98-1.18). Subgroup analyses carried out in Asian and Caucasian population, as well as in population-based and hospital-based controls obtained the same conclusions. Conclusions: No significant correlation is identified between the LTC4S -444 A>C polymorphism and susceptibility to asthma. Researches with high-quality and large sample size are required for further validation in multi-center hospital.